Primary Care Centers Pharmacist Workforce Demand in Eleven Years (2006-2016), and Forecasting in Fifteen Years (2016-2030) at Ministry of Health in Saudi Arabia - Alomi, Yousef Ahmed; Alghamdi, Saeed Jamaan; Alattyh, Radi Abdullah (Journal of Pharmacy Practice and Community Medicine)
Objective: The aim of this study is to explore primary care centers pharmacist workforce demand in eleven years (2006-2016) and projection of primary care center pharmacists demand for coming fifteen years (2016-2030) at Ministry of Health in Saudi Arabia. Methods: It is a retrospective analysis of eleven years (2006-2016) of MOH primary healthcare center (PCC) pharmacist’s workforce demand and projection of primary care center pharmacist’s demand for coming fifteen years (2016-2030) at Ministry of Health in Saudi Arabia. All data were derived from Ministry of Health Statistical Year Books over the past eleven years and Ministry of Health (MOH) standard. It included demand pharmacists or clinical pharmacists’ workforces at MOH primary healthcare centers. All calculations were based on Ministry of Health workforce standards of primary healthcare center. The calculations were per each region for a total of twenty-one regions, the primary health care center distribution numbers, the ratio of pharmacist per PCC, total number of demand pharmacist per each PCC, the expected number of pharmacist requirement in the coming years 2016-2030, primary healthcare center Pharmacist per each region across Saudi Arabia. Results: The total numbers of hospitals were 276 hospitals, 2,325 primary care centers, and 20 administration regions. The total numbers of pharmacists were 3,520 distributed at hospital 2,760 (78.41 %), at primary care centers 430 (12.2 %) while administration regions 330 (9.37 %). The average number of pharmacist per each primary care center pharmacist was (0.077) with a range number of (0.035-0.195). The total average demand primary care center pharmacists were (10,617.18) with range (9,586-11,401) with total number demand was (11,401) primary care center pharmacist. The total demand pharmacists for primary care centers by the year 2030 will be (16,515.79) with range (11,625.00- 16,515.79). Conclusion: Over past several years, there was very high demand of primary care pharmacist in Saudi Arabia. There is a high number of pharmacist jobs in the future. Targeting of implementation of Saudi Vision 2030 including pharmacy new vision are highly recommended in Kingdom of Saudi Arabia.
Keywords: Parenteral nutrition; Pharmaceutical care; Ministry of health; Saudi arabia